(untitled) (Libellarium: journal for research in the field of information and related sciences, 2016)
Electronic books enrich the reading experience through a range of possibilities digital technology offers, such as commenting or adding content at the margin space, marking interesting chapters and sharing the content with other readers. The phenomenon of social reading emerges with the influence of technology in the sphere of reading books and creates interactions for readers with the content and other readers. The great potential of enriching the reading experience is visible in the digital platforms for social reading, where the interaction and the creation of new content encourages the development of new way of reading and creativity. These activities may contribute to better understanding of the text. This enhances the communication about the text thus revitalizing the content and moves the reading itself from private to public sphere. This paper will show how are the activities in the digital margins transformed into a good indicator of the reading behavior, as well as the importance and usefulness of such for publishers to create new publishing products and services.